(untitled) (CIPEEX, 2025)
Introduction: The role of biomedical scientists in extracorporeal perfusion was formally recognized by Biomedicine in April 2007, through Resolution No. 153. This area, which involves extracorporeal circulation, is fundamental in cardiac and vascular surgeries that temporarily take over the function of the heart using equipment. Anatomical knowledge and professional qualifications are extremely important for working in this area. Objective: To conduct a bibliographic study on the role of biomedical scientists in extracorporeal perfusion, highlighting their responsibilities and importance during surgical procedures. Methodology: A narrative bibliographic search was conducted between January and March 2025, using the following keywords: Perfusion (AND); (AND) blood (OR) Extracorporeal Circulation. The searches were conducted in the PubMed database, including complete scientific articles published in Portuguese and English that addressed the professional role in extracorporeal perfusion. Results: The research showed that biomedical perfusionists play a crucial role in preserving the patient’s vital functions during cardiovascular surgical procedures. They are responsible for operating, monitoring, and maintaining the extracorporeal circulation machine, controlling variables such as blood flow, oxygenation, and body temperature. Their work contributes directly to patient safety and the success of the surgical procedure, requiring technical knowledge and teamwork with a multidisciplinary team. Conclusion: The biomedical perfusionist is essential in highly complex procedures, being responsible for ensuring ideal physiological conditions for the patient during temporary interruption of cardiac function. Their skilled work contributes significantly to good clinical outcomes.